Inhibiting Monoacylglycerol Lipase Suppresses RANKL-Induced Osteoclastogenesis and Alleviates Ovariectomy-Induced Bone Loss - Liu, Hui; Zhou, Chuankun; Qi, Dahu; Gao, Yutong; Zhu, Meipeng; Tao, Tenghui; Sun, Xuying; Xiao, Jun (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis is a common chronic metabolic bone disease characterized by reduced trabecular bone and increased bone fragility. Monoacylglycerol lipase (MAGL) is a lipolytic enzyme to catalyze the hydrolysis of monoglycerides and specifically degrades the 2-arachidonoyl glycerol (2-AG). Previous studies have identified that 2-AG is the mainly source for arachidonic acid and the most abundant endogenous agonist of cannabinoid receptors. Considering the close relationship between inflammatory mediators/ cannabinoid receptors and bone metabolism, we speculated that MAGL may play a role in the osteoclast differentiation. In the present study, we found that MAGL protein expression increased during osteoclast differentiation. MAGL knockdown by adenovirus-mediated shRNA in bone marrow-derived macrophages demonstrated the suppressive effects of MAGL on osteoclast formation and bone resorption. In addition, pharmacological inhibition of MAGL by JZL184 suppressed osteoclast differentiation, bone resorption, and osteoclast-specific gene expression. Activation of the MAPK and NF-κB pathways was inhibited by JZL184 and deletion of MAGL. Our in vivo study indicated that JZL184 ameliorated bone loss in an ovariectomized mouse model. Furthermore, overexpressing H1 calponin partially alleviated the inhibition caused by JZL184 or MAGL deletion on osteoclastogenesis. Therefore, we conclude that targeting MAGL may be a novel therapeutic strategy for osteoporosis.